Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae) - Lin, Mei-Ying; Lingafelter, Steven W. (Zootaxa, 2018)
Paragniopsis ochraceomaculata Breuning, 1965 and Paragniopsis Breuning, 1965 are confirmed to be junior synonyms of Agnioides striatopunctatus Breuning, 1956 and Agnioides Breuning, 1956 respectively after comparison of types; Monochamus fruhstorferi Breuning, 1964 is a new junior synonym of Annamanum lunulatum (Pic, 1934). Paranamera ankangensis Chiang, 1981 and Mimonemophas multimaculatus Xie & Wang, 2015 are transferred to the genus Anoplophora Hope, and the former is newly recorded from Hunan Province.